Pembelajaran Mitigasi Bencana Melalui Media Audio Visual Pada Kelas X di SMA Negeri 10 Semarang - Rochmah, Aini Nur Khoirurrizqi; Sriyono, Sriyono; Aji, Ananto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2018)
Audio visual media helps teachers in the learning process. The purpose of this study are to know the activity and analyze the learning outcomes of students of class X in learning disaster mitigation through audio visual media. This research is a quantitative descriptive research. The population are a class X student IPS of four classes, and sample are two classes. Sampling technique using purposive sampling. Data collection techniques are observation, documentation and test. Data analysis used descriptive percentage and inferential statistics. The results of research are; (1) student activity is good enough category with average control class percentage 40,88% and experiment class 47,82%, (2) student learning result increase with t value 13,46 whereas t-table value 0,678 at level error 5%, then the value (t arithmetic> t table) so that there are differences in learning outcomes between the control class and the experimental class. The conclusions in this study are good student learning activities and student learning outcomes are quite good. Suggestions put forward audio visual media as one of the alternative ways that teachers use to support the process of learning media based education as an effort to improve student activity and learning outcomes. Media audio visual membantu guru dalam proses pembelajaran. Tujuan penelitian ini adalah untuk mengetahui aktivitas dan menganalisis hasil belajar siswa kelas X dalam pembelajaran mitigasi bencana melalui media audio visual. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasi adalah siswa kelas X IPS berjumlah empat kelas, dan sampel sebanyak dua kelas. Teknik pengambilan sampel menggunakan purposive sampling. Teknik pengumpulan data yaitu observasi, dokumentasi dan tes. Analisis data menggunakan deskriptif presentase dan statistik inferensial. Hasil penelitian yaitu; (1) aktivitas siswa termasuk kategori cukup baik dengan rata-rata persentase kelas kontrol 40,88% dan kelas eksperimen 47,82%, (2) hasil belajar siswa meningkat dengan nilai t hitung 13,46 sedangkan nilai t-tabel 0,678 pada taraf kesalahan 5%, maka nilai (t hitung> t tabel) sehingga ada perbedaan hasil belajar antara kelas kontrol dan kelas eksperimen. Simpulan dalam penelitian ini aktivitas belajar siswa cukup baik dan hasil belajar siswa tergolong baik. Saran yang diajukan media audio visual sebagai salah satu cara alternatif yang digunakan guru untuk menunjang proses pembelajaran berbasis media pendidikan sebagai upaya meningkatkan aktivitas dan hasil belajar siswa